Scabies as a Health Challenge in Coastal Areas and Its Control strategie, Indonesia : A Review - Yulya Lasmita; Tuljannah, Magvirah (Journal of Epidemiology and Health Science, 2026)
Background: Scabies is a contagious parasitic skin disease caused by Sarcoptes scabiei and remains a significant public health concern, particularly in settings characterized by inadequate water sanitation, limited access to healthcare, and high population density. Although it is commonly associated with low-resource environments, scabies affects populations globally, contributing to considerable morbidity, especially among children in coastal and densely populated communities. Poor environmental conditions and limited awareness regarding personal hygiene further exacerbate its transmission. Objective: This study aims to identify factors associated with the incidence of scabies, particularly in relation to environmental sanitation, personal hygiene, and population density in coastal regions. Methods: This study employed a systematic literature review approach by analyzing peer-reviewed journal articles focusing on scabies in coastal environments and high-density populations. Relevant studies were identified, screened, and synthesized to obtain comprehensive evidence regarding associated risk factors and effective control strategies. Results: The findings indicate that poor personal hygiene, inadequate sanitation facilities, and overcrowded living conditions are major contributors to the increased incidence of scabies. In addition, limited health education and restricted access to clean water further facilitate disease transmission. Effective control strategies include health education interventions, improvements in water and sanitation infrastructure, and medical treatments such as mass drug administration using ivermectin or topical permethrin. Conclusion: Comprehensive community-based interventions integrating health education, environmental sanitation improvements, and appropriate medical treatment are essential to reduce the burden of scabies, particularly in vulnerable coastal populations. Keywords: scabies, coastal areas, sanitation, health education, control strategies, Indonesia